Drought Disaster Causes and Their Proposed Adaptation Strategies around Karst Areas in Gunungkidul Regency, Indonesia : A Review - Wahyu Endah Christiani Putri; Akhmad Zamroni; Andrea Sumarah Asih; Haris Nur Eka Prasetya; Saurina Tua Sagala; King Joshua Almadrones-Reyes (Department of Geography Education, University of Jember, 2024)
Gunungkidul Regency, one of Indonesia's karst regions, frequently experiences droughts. This study aims to investigate the causes of drought disasters and provide adaptation strategies for disasters that may occur near karst areas in Gunungkidul Regency. We used Google Scholar to identify drought causes on the study site. The next stage is making appropriate adaptation strategies using a qualitative and comparative analysis technique. The three main components that cause drought disasters in Gunungkidul Regency include climate characteristics, hydrogeological characteristics, and anthropogenic factors. Some proposed adaptation strategies to address the impacts of drought disasters include planting crops with low water requirements, adopting conservation agriculture and utilizing organic farming, applying structural adaptation strategies, developing agroforestry, giving farmers financial assistance, paying compensation to drought-affected families, distributing knowledge about drought adaptation strategies, reducing family food demand, suggesting seasonal migration, and reducing livestock. Working with multiple stakeholders is essential to putting these adaptation strategies into action.